PENGARUH PERHATIAN ORANG TUA TERHADAP TINGKAT STRES SISWA - Siti Khairani; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to identify parents 'attention to students, 2) To determine students' stress level, 3) To describe the attention of parents, 4) To describe the stress level of students, 5) To know how much influence the attention of the person Old to the stress level of students. The subjects of the study were all students of class VII of SMP Negeri 8 Pekanbaru which amounted to 375 people, but the researchers only took 50% of the students of grade VII. Determination of sample by using Random Sampling technique. Where researchers chose class VII students because of the results of the phenomenon and AUM-U which has spread the number of students who experience stress. The results showed that the picture of parents attention 29.26% almost half still less attention, and the picture of stress levels of students 62.77% more than half of students experience a moderate level of stress. The results of correlation coefficient calculations X1 and X2 is -549 and the coefficient of determination 0.298 this shows the effective contribution of parents attention to the stress level experienced by 29.8%. Hypothesis test states there is a significant negative effect of attention of parents to the level of stress experienced by students of class XII SMP Negeri 8 Pekanbaru.Keywords: Parental concern, stress level